2017
DOI: 10.1161/circoutcomes.115.002458
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Smoking Cessation Interventions in Patients With Cardiovascular Disease

Abstract: 1T he efficacy and safety of pharmacological and behavioral smoking cessation interventions have been examined in multiple randomized controlled trials (RCTs), with subsequent meta-analyses showing that such interventions are efficacious at increasing quit rates.1,2 However, participants in these trials were generally healthy, and the generalizability of these data to patients with cardiovascular disease (CVD) is unclear. This unclear generalizability is underscored by 3 trials that found that the smoking cess… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
45
0
10

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 86 publications
(60 citation statements)
references
References 57 publications
5
45
0
10
Order By: Relevance
“…[11][12][13] Along with bupropion, varenicline has been shown to increase abstinence in patients with stable cardiovascular disease; however, its efficacy in patients with acute coronary syndrome was previously unknown. 6 We have recently shown that use of varenicline increases smoking abstinence 24 weeks after acute coronary syndrome. 14 Here we report evidence concerning the efficacy and safety of varenicline for smoking cessation 52 weeks after acute coronary syndrome.…”
mentioning
confidence: 99%
“…[11][12][13] Along with bupropion, varenicline has been shown to increase abstinence in patients with stable cardiovascular disease; however, its efficacy in patients with acute coronary syndrome was previously unknown. 6 We have recently shown that use of varenicline increases smoking abstinence 24 weeks after acute coronary syndrome. 14 Here we report evidence concerning the efficacy and safety of varenicline for smoking cessation 52 weeks after acute coronary syndrome.…”
mentioning
confidence: 99%
“…Because these symptoms are largely relieved with NRT, increased use of NRT should improve quality of care and patient experience for many smokers,32, 33, 34 and should also help avoid nicotine withdrawal‐associated delirium 35, 36. Second, because inpatient NRT use has been associated with greater outpatient NRT use13 and NRT is a well‐accepted and generally effective treatment for smoking cessation,37, 38 greater use of NRT in the inpatient setting should positively influence long‐term smoking cessation rates 14. Third, because the Joint Commission now considers prescription of pharmacotherapy for smoking cessation (of which the vast majority is NRT) a standard of care for both inpatient use and at hospital discharge,39 and patient motivation to quit smoking is high after a hospitalization, we believe that hospitals can pursue quality initiatives40 to ensure that all hospitalized smokers are offered and prescribed smoking cessation medications to improve smoking cessation outcomes and to meet Joint Commission performance measures.…”
Section: Discussionmentioning
confidence: 99%
“…Телефонное консультирование способствовало отказу от курения в течение 6 и более месяцев в 1,47 раз (95% ДИ 1,15-1,88), а индивидуальное консульти-рование -в 1,64 раза (95% ДИ 1,17-2,28), при этом короткий совет медицинского работника отказаться от курения в большинстве случаев к значимому результату не приводил: ОШ =1,05, (95% ДИ 0,78-1,43). Авторы связывают это с формальным подходом медицинских работников и отсутствием знаний по проведению когнитивно-поведенческой терапии [32]. Авторы делают вывод о необходимости назначе-ния варениклина и бупропиона для лечения никоти-новой зависимости у больных ССЗ.…”
Section: Smoking Influence On the Outcomes And Complications Of Coronunclassified